HOTTIP Enhances Gemcitabine and Cisplatin Resistance Through Sponging miR-637 in Cholangiocarcinoma - Gao, Kun; Chen, Shuhua; Yang, Xiangyu (Frontiers in Oncology, 2021)
Chemo-resistance prominently hampers the effects of systemic chemotherapy to cholangiocarcinoma (CCA). Long non-coding RNAs (lncRNAs) have been shown to have great importance not only in tumorigenesis but also in therapeutic prognosis. The aim of this study is to investigate the role of lncRNA HOTTIP in the chemo-resistance to cisplatin and gemcitabine (CG) in CCA. The upregulated expression of HOTTIP was observed in CCA patients and the upregulation was associated with therapeutic responsiveness and prognosis. HOTTIP silencing powerfully increased the chemotherapy sensitivity through weakening proliferation and colony formation and increasing apoptosis. Subsequently, miR-637 was identified as the functional target of HOTTIP, since mechanically it could be targeted by HOTTIP and functionally its overexpression dismissed the changes by HOTTIP silencing in vitro and in vivo. Moreover, LIM and SH3 domain protein 1 (LASP1) could be targeted and regulated by miR-637. In all, HOTTIP modulates the sensitivity to CG in CCA through the HOTTIP/miR-637/LASP1 regulatory axis, providing a new opportunities for CCA treatment.